Realization of 18.97% theoretical efficiency of 0.9 μm thick c-Si/ZnO heterojunction ultrathin-film solar cells via surface plasmon resonance enhancement. Issue 8 (9th February 2022) - Zhao, Fei; Lin, Jiangchuan; Lei, Zhenhua; Yi, Zao; Qin, Feng; Zhang, Jianguo; Liu, Li; Wu, Xianwen; Yang, Wenxing; Wu, Pinghui
Abstract : We propose an ultrathin-film c-silicon (silicon is 0.9 μm)/ZnO heterojunctions solar cells. It has been found that the average absorption in the wavelength range from 300 to 1400 nm reaches 93.16%. The short circuit current density ( J sc ) reached 41.94 mA cm −2 . The efficiency of the solar cell reaches 18.97%. Abstract : In this work, we demonstrate that the performance of c-Si/ZnO heterojunction ultrathin-film solar cells (SCs) is enhanced by an integrated structure of c-Si trapezoidal pyramids on the top of a c-Si active layer and Al pyramids in the active layer on the Al back electrode. The top c-Si trapezoidal pyramid (TTP) increases the absorption of short wavelengths by lengthening the propagation distance of incident light and coupling the incident light into photonic modes in the active layer. The bottom Al pyramid (BP) improves the overall optical absorption performance especially for the long wavelength band by forming the surface plasmon resonance (SPR) mode in the active layer. As a result, the average absorption in the entire wavelength range (300–1400 nm) reaches 93.16%. The optimized short-circuit current density ( J sc ) and photoelectric conversion efficiency (PCE) of ultra-thin film c-Si/ZnO SCs are 41.94 mA cm −2 and 18.97%, respectively. Moreover, the effect of different illumination angles on the optical absorption of the SCs was explored. The SCs have good absorption when the incident angles are in the range from 0 degrees to 60 degrees. Furthermore, the underlying mechanism for the enhancement of photon absorption in the SCs was discussed through careful analysis of the electric field intensity profile at different wavelengths. It was found that the electric field tends to concentrate around the bottom pyramids and top trapezoidal pyramids even for the long-wave band, which results in an excellent light-trapping performance.